2015
DOI: 10.1111/tid.12348
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir and simeprevir combination therapy in the setting of liver transplantation and hemodialysis

Abstract: We report safety, tolerability, and 12-week sustained virologic response with half-standard dose sofosbuvir and standard-dose simeprevir combination therapy in a hepatitis C virus genotype 1a-infected liver transplant recipient on hemodialysis - uncharted territory for sofosbuvir-based therapy. The patient was a non-responder to prior treatment with pegylated interferon plus ribavirin. Sofosbuvir efficacy was maintained despite pill-splitting and administration of half-standard dose, 200 mg per day. No drug-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 4 publications
3
36
0
5
Order By: Relevance
“…This study included traditionally difficult to treat patients, with 43% being previously treated nonresponders and 52% being either transplant recipients or having decompensated cirrhosis. The SVR rate in this study compares favorably to those reported in other studies, which vary widely from 67% to 100%16, 17, 18, 19, 20, 21, 22, 23 (Table 2). Several aspects of these other studies may have contributed to reduced SVR rates, including the use of reduced‐dose SOF18, 19, 20 and the use of regimens with less potential to achieve SVR, such as SOF/RBV and SOF/pegylated interferon/RBV 16, 17…”
Section: Discussionsupporting
confidence: 83%
“…This study included traditionally difficult to treat patients, with 43% being previously treated nonresponders and 52% being either transplant recipients or having decompensated cirrhosis. The SVR rate in this study compares favorably to those reported in other studies, which vary widely from 67% to 100%16, 17, 18, 19, 20, 21, 22, 23 (Table 2). Several aspects of these other studies may have contributed to reduced SVR rates, including the use of reduced‐dose SOF18, 19, 20 and the use of regimens with less potential to achieve SVR, such as SOF/RBV and SOF/pegylated interferon/RBV 16, 17…”
Section: Discussionsupporting
confidence: 83%
“…After screening and reviewing abstracts, 71 studies were excluded according to exclusion criteria. Seven studies were relevant, of which one case report and two case series were excluded (27)(28)(29). Finally, only four clinical studies were included for meta-analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…SVR12 rates were not different between 12 or 24 wk of treatment, with or without RBV, and comparing naive patients to experienced (95% vs 91%) [87,88] . In this small study, the regimen SOF plus SMV with or without RBV was well tolerated; the most common side effects were headache, fatigue, and nausea, and only four (2%) patients discontinued treatment due to these events.…”
Section: Second-generation Pismentioning
confidence: 99%
“…In post-liver transplant patients with HCV infection, co-administration of SMV with cyclosporine resulted in significantly elevated SMV levels, so it is not recommended [87] . SMV can be safely administered with tacrolimus or sirolimus.…”
Section: Second-generation Pismentioning
confidence: 99%
See 1 more Smart Citation